Dissecting binding of a β-barrel membrane protein by phage display. Issue 8 (19th June 2017) - Meneghini, Luz M.; Tripathi, Sarvind; Woodworth, Marcus A.; Majumdar, Sudipta; Poulos, Thomas L.; Weiss, Gregory A.
Abstract : Membrane proteins (MPs) contribute to a myriad of cellular functions. Phage-display of the TonB dependent transporter and MP, ShuA, allows its rapid mutagenesis for structure-function studies. Abstract : Membrane proteins (MPs) constitute a third of all proteomes, and contribute to a myriad of cellular functions including intercellular communication, nutrient transport and energy generation. For example, TonB-dependent transporters (TBDTs) in the outer membrane of Gram-negative bacteria play an essential role transporting iron and other nutrients into the bacterial cell. The inherently hydrophobic surfaces of MPs complicates protein expression, purification, and characterization. Thus, dissecting the functional contributions of individual amino acids or structural features through mutagenesis can be a challenging ordeal. Here, we apply a new approach for the expedited protein characterization of the TBDT ShuA from Shigella dysenteriae, and elucidate the protein's initial steps during heme-uptake. ShuA variants were displayed on the surface of an M13 bacteriophage as fusions to the P8 coat protein. Each ShuA variant was analyzed for its ability to display on the bacteriophage surface, and functionally bind to hemoglobin. This technique streamlines isolation of stable MP variants for rapid characterization of binding to various ligands. Site-directed mutagenesis studies targeting each extracellular loop region of ShuA demonstrate no specific extracellular loop is required for hemoglobin binding. Instead two residues, His420 and His86 mediate this interaction. The results identify a loop susceptible to antibody binding, and also a small molecule motif capable of disrupting ShuA from S. dysenteriae . The approach is generalizable to the dissection of other phage-displayed TBDTs and MPs.